Legal Instruments of the Protection from Waters (Floods and Droughts) and of the Protection of Waters - Szalma, József (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
In this paper the author analyzes the Serbian law, the laws of several European countries (Germany, France, Austria, Hungary and Croatia) and European Union rules in respect of the protection from harmful effects of waters, such as floods, erosion, torrents, icing on the surface of waters, just as well as the rules on diverting of water from a territory where it is in surplus, on the one hand, or directing it from the territory where it is in surplus to the one with water shortage (amelioration), on the other. The subject of analysis is the instruments of water management in the function of protection from high-water, too, such as the long and short term planning of protection from floods, measures necessary to prevent them and elimination of their effects. The maintenance of required water regime is also considered as an instrument of protection from high-water, especially the construction and upkeep of facilities for protection from floods. Facilities for utilization of water resources, such as roads and bridges, should be constructed in accordance with environmental permits, at the level well above the high water level measured in a longer period of time.